Soil Quality Impacted by Brick Kilns in the Agriculture Fields of Kathmandu Valley - Koirala, Melina; Sapkota, Ramesh Prasad; Pradhanang Kayastha, Sadhana (Journal of Environment Sciences, 2025)
Brick kilns are causing environmental concerns due to their potential negative impacts on soil health and heavy metal accumulation in the agricultural soils. However, there are limited studies reflecting the impacts on agricultural soils due to the operation of brick kilns in the Kathmandu Valley, Nepal. Therefore, this study aims to assess the impact of the kilns on soil health in Lalitpur and Bhaktapur districts of Kathmandu Valley, focusing on soil parameters pH, nitrogen, phosphorus, potassium, moisture content, organic carbon, and heavy metals (Pb and Zn). Standard methods were used for the determination of soil quality parameters. Twelve brick kilns (six from each district) were studied, with 36 soil samples (0-15 cm depth) collected at 100 m, 200 m, and 300 m from each kiln. Results showed low levels of organic matter, carbon, nitrogen, potassium, and moisture near the proximity of the brick kiln areas, i.e., in most of the 100 m distance sites compared to 300 m sites. Soil excavation for brick production and kiln emissions are degrading agricultural land, gradually harming key soil fertility over time. Lead (not detectable-32.04 mg/kg) and zinc (22.44-143.16 mg/kg) concentrations in soil samples were in the commonly observed natural range, and the geo-accumulation index indicated low lead and high zinc contamination. Soil quality parameters were in improved conditions moving the distance from the kilns, suggesting the impact of emissions and nearby soil excavation for brick production. Alternatives to brick uses and production are required to be identified for the conserving the fertile top soils of the agricultural lands.